A STUDY ON THE ROLE OF CHIT FUNDS AS MULTIFACET FINANCIAL COMPANIES IN THE STATE OF ANDHRA PRADESH - Santhisree, Dr V.N. (The journal of contemporary issues in business and government, 2022)
Chit fund institution is indigenous, simple, easy, readily understood, and widely accepted by rural and urban middle-class people. It is a popular borrowing instrument. The aim is to pool small savings managed by a foreman who acts as a trustee-cum-supervisor for the process of collection and allotment for the pooled amount to catch members by rotation. Chit funds represent an ancient form of savings and credit institution before the banking system in rural India. Most of the financial needs of rural and urban middle-class people are taken care of by Chit funds. They meet their specific needs for large family functions, festivals, education, housing, agriculture, business, and medical expenses: most people, irrespective of urban and rural, avail this avenue for reasonable returns. Chit funds offer complete parallel banking services as a vast network of small business people, homemakers and salaried individuals. The popularity of chit funds has not been affected by the increased awareness of the mutual funds and equity market. The chit funds played a crucial role in the Indian financial system and worked as a bridge between the age-old financial practices and the modem banking system. Today chit fund in India is highly standardized and stands in the financial industry's status. Even after the enormous expansion of bank branches all over the country, chit funds continue to exist and expand more popularly than banks in many regions of the country.